Women and political power in latin america: A reflection from the XXIst-century viewpoint [Mujer y poder político en Latinoamérica: Una reflexión desde el siglo XXI] - Rincón Soto, Lucía (2015)
This work consists of a reflection, from the twenty-first century viewpoint, about the incipient role of women in spaces of political power in Latin America. It is based on the premise that women have few probabilities of exercising leadership in this patriarchal society, since on this road to power, they have more challenges than men to arrive and maintain themselves there. On the other hand, it is proposed that, even though women seek to consolidate themselves in spheres of command, currently, this does not necessarily translate into better advantages for the rest of the women who are not in the public-political sphere.